Facial Talon Cusp - A Rare Entity - Preeti P Nair; Shaji Thomas (Wolters Kluwer Medknow Publications, 2004)
A talon cusp is an accessory cusp which commonly occurs on the lingual surface of incisors. The unusual location of this cusp on the facial surface can pose a challenge in the correct diagnosis and management. A case report of the same with a review of literature has been presented here.